UPAYA PEMBERIAN PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA AKIBAT TINDAKAN PASSING OFF TERHADAP HAK MEREK DAGANG DALAM SISTEM HUKUM MEREK DI INDONESIA - Julianti, Lis; Septiovita, Erma (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2017)
Passing off is a form of unfair competition which can lead to confusion, and false allegation, because with the passing off the impression there is a close link / indication of the existence of a relationship, an indication of misleading the public (consumers). The absence of laws that specifically regulate the Passing Off action as a violation on Trademark Rights resulted in businesses that are victims of this action is difficult to obtain legal protection. Efforts to provide legal protection to businesses as a result of act of unfair competition in the form of passing off against the trademark rights is still in general in the Criminal Code Article 372 bis Penal (Penal Code).